Pemanfaatan Short Message Service Berbasis Seluler dalam Meningkatkan Pengetahuan dan Sikap terhadap Seks Pranikah pada Remaja - Yuni Kusmiyati Hari Kusnanto Mohammad Hakimi (Berita Kedokteran Masyarakat (BKM), 2011)
Background: Many adolescents are involved in early sexual activities and perhaps with multiple partners. Pre-marital behavior can lead to unwanted pregnancy, sexually transmitted infection, abortion, fertility and mortality. Knowledge and less supporting attitude on pre-marital sexual activities as well as less access to information are believed to be the factors on high pre-marital sexual problems among adolescents.Objective: Known effectiveness of Cellular-Based Short Message Service (SMS) in increasing knowledge and attitude on pre-marital sex among adolescents in Yogyakarta Municipality.Method: This study used Randomized Controlled Trials (RCT) with pre-post study design. Samples were 227 students in the 10th grade from SMAN 7 and SMAN 10 of Yogyakarta. Data analysis used Paired t-test, Independent samples T-test, Anova and Linear regression with ρ=<0.05 and 95% CI.Result: The analysis result showed that pre-marital SMS at 7 pm-9 pm resulted in knowledge mean difference of 1.33 (ρ=0.00<0.05) with 95% CI (0.46-2.19) and attitude mean difference of 3.47 (ρ=0.00<0.05) with 95% CI (1.39-5.43) while pre-marital SMS at 9 am-11 am resulted in knowledge mean difference of 1.47 (ρ=0.00<0.05) with 95% CI (0.79-2.15) and attitude mean difference of 4.22 (ρ=0.00<0.05) with 95% CI (2.91-5.54). Control group 1 presented knowledge mean difference of -0.16 (ρ=0.66>0.05) with 95% CI (-0.89-0.58) attitude mean difference of -0.41 (ρ=0.75>0.05) with 95% CI (-1.61-0.80) while control group 2 presented knowledge mean difference of 0.09 (ρ=0.9>0.05) with 95% CI (-0,25-0.45) and attitude mean difference of -0.46 (ρ=0.85>0.05) with 95% CI (-1.27-0.34).Conclusion: SMS is effective in increasing adolescents’ knowledge and attitude on pre-marital sex in Yogyakarta Municipality. There is no effectiveness difference of giving an SMS at the different times to increase adolescents’ knowledge and attitude on pre-marital sex.Keywords: SMS, seluler, knowledge, attitude, pre-marital sex, adolescent